Size and surface effects in the magnetic order of CoFe2O4 nanoparticles - Pianciola, Betiana Noelia (2015)
In this work, we have focused on the size dependence of the magnetic properties and the surface effects of CoFe2O4 nanoparticles synthesized by high-temperature chemical method with diameter d~2, 4.5, and 7 nm, with narrow size distribution. transmission electron microscopy (TEM) images and X-ray diffraction (XRD) profiles indicates that samples with 7 and 4.5 nm present a high crystallinity while the 2 nm sample has a poor one. We have investigated by magnetization measurements and in-field Mössbauer spectroscopy the influence of the surface in the internal magnetic order of the particles. Particles with d=7 nm have almost single domain behavior and the monodomain occupies approximately the whole particle. In the sample with d=4.5 nm the surface anisotropy is large enough to alter the ferrimagnetic order in the particle shell. Then, a surface/volume ratio of ~60% is the crossover between a single domain nanoparticle and a frustrated order in a magnetic core-shell structure, due to the competition between surface anisotropy and exchange interaction+crystalline anisotropy in cobalt ferrite. In the d=2 nm sample the poor crystallinity and the large surface/volume ratio avoid the ferrimagnetic order in the particle down to T=5 K.